Docking and antidermatophytic studies of azadirachta indica With aloe barbadensis against trichophyton species - C. BANU REKHA,; DR. D. LATHA,; DR. S.VIJAYALAKSHMI, (International Journal of Pharma and Bio Sciences, 2017)
The study was to assess the antidermatophytic activity of the ethanol, ethyl acetate and aqueous extract of Neem (Azadirachta indica) and Aloe vera (Aloe barbadensis ) against dermatophytes isolated from different soil. Dermatophytes were identified, Out of 156 samples, 42 isolates of Trichophyton mentagrophytes, 37 isolates of Trichophyton rubrum, 27 isolates of Trichophyton terrestre, 21 isolates of Trichophyton tonsurans, and 18 isolates of Trichophyton verrucosum were isolated and identified. We selected two most common pathogen among the Trichophyton species, i.e., Trichophyton mentagrophytes and Trichophyton rubrum to find the antidermatophytic activity of Plant extracts. The minimum inhibitory concentration (MIC) by broth dilution method and minimum fungicidal concentration (MFC) with the leaf extracts of the plants Azadirachta indica and Aloe barbadensis against the isolated dermatophytes was determined. Among the Trichophyton species, The MIC of the combination of ethyl acetate extract of Azadirachta indica with Aloe barbadensis shows the least MIC valve of 62.5µg/ml, to inhibit T. mentagrophytes and 125µg/ml against the growth of T. rubrum. Controls were maintained. The GC-MS chromatogram analysis of combined Azadirachta indica with Aloe barbadensis showed the presence of eight components based on their molecular weight and retention time. Phytol derivative shows the highest peak at a retention time of 18.83. In silico molecular docking was carried out to find the molecular interaction analysis of four compounds (phytol, heptadecanoic acid, isopropyl stearate and docosanoic acid) against glucan1,3- beta glucosidase and subtilisin like protease 3 using Autodock software. These two proteins selected for our study are which was an extracellular protease secreted due to the dermatophytic infection. Among the four ligands, phytol shows good interactions with least energy against drug target hence it may act as potent inhibitor against T. mentagrophytes and T. rubrum. The results prove that combination of Azadirachta indica with Aloe barbadensis can be used to develop a novel drug formulation against tinea infection. The insilico studies can be further analysed for innovative and informative treatment methods.